Multiple-injection dry low-NOx combustor for hydrogen-rich syngas fuel: testing and evaluation of performance in an IGCC pilot plant - Tomohiro ASAI (The Japan Society of Mechanical Engineers, 2014)
The successful development of oxygen-blown integrated coal gasification combined cycle (IGCC) technology requires gas turbines capable of achieving the dry low nitrogen oxides (NOx) combustion of hydrogen-rich syngas for low emissions and high plant efficiency. The authors have been developing a “multiple-injection burner” to achieve the dry low-NOx combustion of hydrogen-rich syngas. This burner consists of multiple fuel nozzles and a perforated plate with multiple air holes. At each injection point, one fuel nozzle and one air hole are installed coaxially, so that a fuel jet surrounded by a sheath air jet is injected. The burner achieves low-NOx combustion by mixing fuel and air rapidly with multiple fuel-air coaxial jets, and prevents flashback into the burner by lifting the flame from itself. The purpose of this paper is to present the test results of multi-can combustors equipped with multiple-injection burners in an IGCC pilot plant, and evaluate combustor performance by focusing on the effects of flame shapes. The syngas fuel produced in the plant contained approximately 50% carbon monoxide, 20% hydrogen, and 20% nitrogen by volume. In the tests, the combustor with slenderer flames achieved lower NOx emissions of 10.9 ppm (at 15% oxygen) diluent-free with high stability and high reliability, and reduced both combustor liner and burner plate metal temperatures at the maximum gas turbine load. These findings demonstrated that the multiple-injection combustor achieved the dry low-NOx combustion of the syngas fuel in the plant.